The search for the real Mt. Sinai. - Greisen, Steve; Rhys, John (Reel Productions, Monument, CO, 1999)
Two explorers take an incredible expedition into the blistering Arabian desert and turn up what many scholars believe to be one of the greatest discoveries in history...the real mount Sinai, the holy mountain on which Moses received the ten commandments
This program tells their amazing story how they crawl into forbidden military installation, and use night vision goggles to avoid being detected as they pursue their mission and discover over a dozen significant remnants still remaining at the site. The explorers embark on a journey that would change their lives forever... finding remarkable evidence that confirms the Bible as historically accurate.
Keywords: Sinai, Mount (Egypt); Bible -- Antiquities; Archaeology